OOxytetracycline Hydrochloride (OTC-HCl) Application for Control of Palm Phytoplasmas - Brian W. Bahder; Ericka E. Helmick (EDIS)
Phytoplasma diseases of palms are a major threat to the Florida nursery and landscaping industries.  Historically, lethal yellowing (LY) has been responsible for the death of millions of coconut palms throughout the Caribbean.  LY, introduced into Florida sometime in the first half of the 20th century, has been causing decline of over 30 species of palm (Harrison and Elliott 2015).  In 2006, lethal bronzing disease (LBD) was discovered on the west coast of Florida near Tampa.  Currently, the only two management options available for control of phytoplasmas is an aggressive sampling strategy followed by consistent tree removal and injections of OTC.  This document seeks to provide a source of information and instruction on the injection of OTC into palm trunks.